4th International Conference on Biomedical Engineering in Vietnam - Toi, Vo Van.; Toan, Nguyen Bao.; Dang Khoa, Truong Quang; Lien Phuong, Tran Ha.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume presents the proceedings of the Fourth International Conference on the Development of Biomedical Engineering in Vietnam which was held in Ho Chi Minh City as a Mega-conference. It is kicked off by the Regenerative Medicine Conference with the theme (3z(BBUILDING A FACE(3y (BUSING A REGENERATIVE MEDICINE APPROACH(3y(B, endorsed mainly by the Tissue Engineering and Regenerative Medicine International Society (TERMIS). It is followed by the Computational Medicine Conference, endorsed mainly by the Computational Surgery International Network (COSINE) and the Computational Molecular Medicine of German National Funding Agency; and the General Biomedical Engineering Conference, endorsed mainly by the International Federation for Medical and Biological Engineering (IFMBE). It featured the contributions of 435 scientists from 30 countries, including: Australia, Austria, Belgium, Canada, China, Finland, France, Germany, Hungary, India, Iran, Italy, Japan, Jordan, Korea, Malaysia, Netherlands, Pakistan, Poland, Russian Federation, Singapore, Spain, Switzerland, Taiwan, Turkey, Ukraine, United Kingdom, United States, Uruguay and Viet Nam.s
Keywords: Engineering; Medical records -- Data processing; Biology -- Data processing; Biomedical engineering; Engineering; Biomedical Engineering; Computer Appl. in Life Sciences; Medical and Radiation Physics; Health Informatics